Test Case Automation: Transforming Software Testing in the Digital Era - Agarwal, Giriraj (International Journal of Computing and Engineering, 2024)
Purpose: This research aims to explore the limitations of manual software testing, the effectiveness of test case automation in addressing these challenges, and the strategies for successful implementation of automation. It also examines the broader impact of adopting test automation on the quality, speed, and efficiency of software delivery. Methodology: The study investigates the challenges of manual testing in agile and DevOps environments and explores the role of automation as a solution. By analyzing various automation tools, frameworks, and best practices, the research provides insights into successful implementation strategies for test case automation. Additionally, it reviews the associated benefits and potential challenges organizations may face when transitioning to automated testing. Findings: Test case automation significantly mitigates the shortcomings of manual testing, particularly in fast-paced development cycles. The findings reveal that automation not only enhances the quality of software by catching defects earlier but also accelerates the testing process, improving overall efficiency. However, the study also identifies challenges, such as the initial investment in tools and skills required for automation, as well as the ongoing need for maintenance of automated test cases. Unique Contribution to Theory, Policy and Practice: This research contributes to the theoretical understanding of software testing (Tom Badgett, Corey Sandler & Glenford J. Myers, 2011) by highlighting the essential role of automation in modern software development methodologies like agile and DevOps. It bridges the gap between traditional manual testing and contemporary automated practices, providing a framework for understanding how automation fits within these rapid development paradigms. In practice, the study encourages organizations to adopt test case automation as a critical policy for improving the quality and speed of software delivery. It offers practical insights into the implementation of automation, including tool selection, training, and process integration, which can guide companies in transitioning to automated testing. Additionally, it highlights the long-term benefits of automation, making it a valuable policy consideration for organizations aiming to optimize their development and testing processes.